Herbal emulgels incorporated with Cola millenii K. Schum stem bark ethanol extract potentially for the management of rheumatoid arthritis in-vitro - Adeola T. Kola-Mustapha; Fahd A. Khalid-Salako (Elsevier, 2021)
Background: Rheumatoid Arthritis (RA) is a chronic autoimmune disease characterized by inflammation and damage of the joints. The current, prevalent treatment options of RA are usually deficient in efficacy, cost-effectiveness and/or are frequently toxic. This is a formulation-oriented study, designed to formulate Cola millenii stem bark extract in an emulgel, suitable for use in the treatment of inflammation associated with RA. Method: The phytochemical analysis and anti-inflammatory activity of Cola millenii stem bark ethanol extract was evaluated using standard analytical methods and Enzyme-Linked Immunosorbent Assay respectively. Inhibitory activity on enzyme/chemokine-substrate reactions involving inflammatory mediators, TNF-α, IL-10, and COX-2 indicated in the pathophysiology of RA were studied. Physical characterization of the formulated emulgels and post-formulation anti-inflammatory studies, using diclofenac emulgel as the positive control were evaluated. Results: The phytochemical analysis of the extract showed the presence of the following phytochemicals: saponins, steroids, anthocyanins, and terpenoids. The extract at concentrations, 2, 4, 6, and 8% w/v, showed dose-dependent anti-inflammatory activity comparable with diclofenac. The formulated emulgels showed good physical characteristics including, easy application and removal, good extrudability, spreadability, pH ranging from 5.06 ± 0.05 to 4.34 ± 0.06 and viscosity ranging from 3.08 ± 0.3 to 3.74 ± 0.4. The formulated emulgels also showed dose-dependent anti-inflammatory activity comparable (p < 0.05) with diclofenac emulgel. Conclusion: The exhibited inhibitory activity of the plant on mediators of inflammation like TNF-α, IL-10, and COX-2 makes it a suitable candidate for formulation in a topical herbal formulation for use in the management of rheumatoid arthritis.